The disappearing body: anorexia as a conflict of embodiment - Fuchs, Thomas (Eating and weight disorders, 2022)
Anorexia nervosa is often regarded primarily as a disorder of the body image, with affected individuals submitting themselves to the dictate of a predominant model of slenderness. However, even though this frequently functions as a gateway to the disorder, the paper intends to show that the actual conflict in anorexia consists in a fundamental alienation of the self from the body. In order to analyze this alienation from a phenomenological point of view, the paper introduces the polarity of lived body (body-as-subject) and physical body (body-as-object). It then explores the phenomenology of anorexia, drawing on characteristic self-reports as well as on the phenomenological, psychoanalytic and cultural science literature. The anorexic conflict of embodiment arises in adolescence, where the body becomes an object of the other's gaze in a special way. Starting with an attempt to comply with the ideal body image, the anorexic patient increasingly fights against her dependency on her body and its uncontrollable nature, above all its hunger and femininity. To be in total control of her body and to gain independence from it, becomes the source of a narcissistic triumph. Thus, in striving for autonomy and perfection, the anorexic patient alienates herself from her embodiment. This results in a radical dualism of 'mind' and 'body': pursuing the ideal of an asexual, angelic, even disappearing body. Anorexia is thus conceived as a fundamental conflict of embodiment.
Online veröffentlicht: 5. März 2021
Gesehen am 17.04.2023